2009
DOI: 10.1103/physrevb.80.245403
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption on theα-Al2O3(0001)surface

Abstract: The adsorption of water monomers, small water clusters, and water thin films on ␣-Al 2 O 3 ͑0001͒ surfaces is studied by density-functional theory. For the metal-terminated surface, the calculations favor the dissociative adsorption for low coverages and the formation of hexagons of alternating dissociatively and molecularly adsorbed water monomers for water-rich conditions. The calculated adsorption energy per water molecule decreases from about 1.5 eV for single adsorbed molecules to about 1.2 eV for thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 39 publications
9
87
1
Order By: Relevance
“…Temperature programmed desorption experiments on Al2O3 in [27,28] have shown that water still desorbs at temperatures above the here-tested 300 °C. Nanosized ceria is able to sorb water as well [29].…”
Section: Microwave-based Detection Of Aging State Dependent Water Adsmentioning
confidence: 61%
“…Temperature programmed desorption experiments on Al2O3 in [27,28] have shown that water still desorbs at temperatures above the here-tested 300 °C. Nanosized ceria is able to sorb water as well [29].…”
Section: Microwave-based Detection Of Aging State Dependent Water Adsmentioning
confidence: 61%
“…This is very similar to the effect of water adsorption at the nonpolar Al 2 O 3 (0001) surface, which was recently found to significantly disrupt the clean Al 2 O 3 surface geometry. 34 We notice that another configuration of very similar energy can be created. In this case, the oxygen of the water molecule again adsorbs close to a surface Li…”
Section: A Zero-coverage Adsorptionmentioning
confidence: 86%
“…It indicates that water adsorption on the ␥-Al 2 O 3 surfaces are stronger than on Cu 2 O surface. On the Al-terminated ␣-Al 2 O 3 (0 0 0 1) surface [45], dissociative adsorption is favored at low water coverage and the formation of hexagons of alternating dissociatively and molecularly adsorbed water monomers is found at high coverage from first principles DFT calculations. The computed free energy profiles from first principles MD simulations show that molecularly adsorbed water is metastable and dissociates readily, even in the absence of defects, by a kinetically preferred pathway at low water coverage [46], while rapid dissociation and unanticipated collective effects, including water-catalyzed dissociation and proton transfer reactions between adsorbed water and hydroxide have been observed at higher water coverage.…”
Section: Water Adsorption On Other Metal Oxide Surfacesmentioning
confidence: 94%